Metal-coordinated sub-10 nm membranes for water purification - You, Xinda; Wu, Hong; Zhang, Runnan; Su, Yanlei; Cao, Li; Yu, Qianqian; Yuan, Jinqiu; Xiao, Ke; He, Mingrui; Jiang, Zhongyi (Nature communications, 2019)
Ultrathin membranes with potentially high permeability are urgently demanded in water purification. However, their facile, controllable fabrication remains a grand challenge. Herein, we demonstrate a metal-coordinated approach towards defect-free and robust membranes with sub-10 nm thickness. Phytic acid, a natural strong electron donor, is assembled with metal ion-based electron acceptors to fabricate metal-organophosphate membranes (MOPMs) in aqueous solution. Metal ions with higher binding energy or ionization potential such as Fe 3+ and Zr 4+ can generate defect-free structure while MOPM-Fe 3+ with superhydrophilicity is preferred. The membrane thickness is minimized to 8 nm by varying the ligand concentration and the pore structure of MOPM-Fe 3+ is regulated by varying the Fe 3+ content. The membrane with optimized MOPM-Fe 3+ composition exhibits prominent water permeance (109.8 L m −2 h −1 bar −1 ) with dye rejections above 95% and superior stability. This strong-coordination assembly may enlighten the development of ultrathin high-performance membranes. Ultrathin membranes have demonstrated great promise for water purification technologies owing to their high permeance. Here the authors fabricate sub-10 nm, defect-free, robust membranes for dye remediation from water through the coordination-driven assembly of metal-organophosphates.